The role of circular RNA in immune response to tuberculosis and its potential as a biomarker and therapeutic target - Hong, Mingyang; Huang, Xu; Zhu, Huiming; Ma, Jiahui; Li, Feng (Frontiers in Immunology, 2025)
Circular RNA (circRNA) is a new type of non-coding RNA that has gained significant attention in recent years, especially in tuberculosis research. Tuberculosis poses a major global public health threat. Its complex pathological mechanisms and worsening drug resistance urgently necessitate new research breakthroughs. The role of circRNA in mycobacterium tuberculosis infection is being gradually revealed, highlighting its importance in regulating gene expression, immune response, and inflammation. Additionally, researchers are interested in circRNA because of its potential for early tuberculosis diagnosis and its role as a biomarker. This article systematically analyzes existing literature to provide new insights into early tuberculosis diagnosis and personalized treatment. We also emphasize the need for future research to enhance the application of circRNA in tuberculosis prevention and control.